A QR code identification technology in package auto-sorting system - Di, Yi-Juan; Shi, Jian-Ping; Mao, Guo-Yong (Modern physics letters. B, Condensed matter physics, statistical physics, applied physics, 2017)
Traditional manual sorting operation is not suitable for the development of Chinese logistics. For better sorting packages, a QR code recognition technology is proposed to identify the QR code label on the packages in package auto-sorting system. The experimental results compared with other algorithms in literatures demonstrate that the proposed method is valid and its performance is superior to other algorithms.